Management of anterior ST-elevation myocardial infarction presenting more than 48 hours from symptom onset without reperfusion therapy in the cardiac care unit - Iswandi Darwis; Anggoro Budi Hartapo; Muhammad Gahan Sarwiko (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
ST-elevation myocardial infarction is a form of acute coronary syndrome that is the leading cause of death worldwide. Treatment with reperfusion therapy in the form of primary percutaneous intervention is the main treatment to reduce morbidity and mortality. However, reperfusion therapy is not recommended for patients presenting with symptoms onset of more than 48 hours. A 62-year-old male patient was diagnosed with anterior STEMI with symptoms onset of more than 48 hours based on complaints of anginal chest pain and shortness of breath. ST-segment elevation in V1-V4 and pathological Q in V1-V3 on ECG and increased hs-Troponin I was reported. The patient was not treated with reperfusion therapy based on treatment recommendations. The patient was given vasodilators, beta-blockers, statins, heparinization, and comorbid infection control in the cardiac care ward. Clinical improvement was obtained, and the patient was discharged after seven days of hospitalization and then was planned for Dobutamine Stress Echo during the follow-up visit. Conservative management and viability testing are the main options for patient management in STEMI with symptom onset of more than 48 hours without any complaints of chest pain, stable hemodynamics, and no life-threatening arrhythmia.